Evaluation of N-P-K-Ca-Mg dynamics in plum (Prunus salicina Lindl.) var. Horvin under nursery conditions (2020)
Temperate fruit trees are a vital part of the economy of the Cundiboyacense highlands in Colombia. The nursery stage is important because it guarantees development at the final grow site. Little is known about the fertilization processes and nutritional dynamics of deciduous fruit trees in the early stages. This research aimed to evaluate the dynamics of N-P-K-Ca and Mg, along with SPAD units, in grafted plum (Prunus salicina) var. Horvin plants under the conditions of tropical highlands, which were evaluated at different growth points (cm), from grafting to transplant. The foliar N concentrations were the highest, followed by the K, P and Mg concentrations. Macronutrient concentrations in the first-stage of grafted nursery plants require nutritional balance for vegetative development and successful establishment at the definitive grow site.